###### Advertisements

###### Advertisements

**Solve the following differential equation:**

`"dy"/"dx" + ("x" - "2y")/("2x" - "y") = 0`

###### Advertisements

#### Solution

`"dy"/"dx" + ("x" - "2y")/("2x" - "y") = 0`

∴ `"dy"/"dx" = - (("x" - "2y")/("2x" - "y"))` ....(1)

Put y = vx

∴ `"dy"/"dx" = "v + x""du"/"dx"`

∴ (1) becomes, `"v + x" "du"/"dx" = - (("x" - "2vx")/("2x" - "vx"))`

∴ `"v + x""du"/"dx" = - ((1 - "2v")/(2 - "v"))`

∴ `"x" "dv"/"dx" = - ((1 - "2v")/(2 - "v")) - "v"`

∴ `"x" "dv"/"dx" = (- 1 + "2v" - 2"v" + "v"^2)/(2 - "v")`

∴ `"x" "dv"/"dx" = ("v"^2 - 1)/(2 - "v")`

∴ `(2 - "v")/("v"^2 - 1)"dv" = 1/"x" "dx"`

Integrating both sides, we get

`int (2 - "v")/("v"^2 - 1)"dv" = int 1/"x" "dx"`

∴ `2 int 1/("v"^2 - 1) "dv" - 1/2 int "2v"/("v"^2 - 1)"dv" = int 1/"x" "dx"`

∴ `2 xx 1/2 log |("v" - 1)/("v" + 1)| - 1/2 log |"v"^2 - 1| = log |"x"| + log "c"_1` .....`[because "d"/"dx" ("v"^2 - 1) = "2v" and int("f"'("x"))/("f"("x")) "dx" = log |"f"("x")| + "c"]`

∴ `log |("v" - 1)/("v" + 1)| - log |("v"^2 - 1)^(1/2)| = log |"c"_1 "x"|`

∴ `log |("v" - 1)/("v" + 1) . 1/sqrt("v"^2 - 1)| = log |"c"_1 "x"|`

∴ `("v" - 1)/("v" + 1) . 1/sqrt("v"^2 - 1) = "c"_1 "x"`

∴ `("y"/"x" - 1)/("y"/"x" + 1) . 1/(sqrt("y"^2/"x"^2 - 1)) = "c"_1 "x"`

∴ `("y" - "x")/("y" + "x") . "x"/sqrt("y"^2 - "x"^2) = "c"_1"x"`

∴ `("y" - "x")/("y" + "x") = "c"_1 sqrt("y"^2 - "x"^2)`

∴ `("y" - "x")/("y" + "x") = "c"_1 sqrt(("y" - "x")("y" + "x")`

∴ `sqrt("y" - "x") = "c"_1 ("y" + "x")^(3/2)`

∴ y – x = `"c"_1^2 ("x + y")^3`

∴ y – x = c(x + y)^{3}, where c = `"c"_1^2`

∴ y = c(x + y)^{3} + x

This is the general solution.

#### APPEARS IN

#### RELATED QUESTIONS

Solve the differential equation (x^{2} + y^{2})dx- 2xydy = 0

Show that the differential equation 2y^{x}^{/y} d*x* + (y − 2*x* e^{x/}^{y}) dy = 0 is homogeneous. Find the particular solution of this differential equation, given that *x* = 0 when y = 1.

Show that the differential equation `2xydy/dx=x^2+3y^2` is homogeneous and solve it.

Show that the given differential equation is homogeneous and solve each of them

(x^{2} + xy) dy = (x^{2} + y^{2}) dx

Show that the given differential equation is homogeneous and solve each of them

(x^{2} – y^{2}) dx + 2xy dy = 0

Show that the given differential equation is homogeneous and solve each of them

`xdy - ydx = sqrt(x^2 + y^2) dx`

Show that the given differential equation is homogeneous and solve each of them

`{xcos(y/x) + ysin(y/x)}ydx = {ysin (y/x) - xcos(y/x)}xdy`

For the differential equations find the particular solution satisfying the given condition:

(x + y) dy + (x – y) dx = 0; y = 1 when x = 1

For the differential equations find the particular solution satisfying the given condition:

`dy/dx - y/x + cosec (y/x) = 0; y = 0 when x = 1`

For the differential equations find the particular solution satisfying the given condition:

`2xy + y^2 - 2x^2 dy/dx = 0; y = 2 " when x " = 1`

A homogeneous differential equation of the from `dx/dy = h(x/y)` can be solved by making the substitution

**A.** *y* = *vx*

**B.** *v* = *yx*

**C.** *x *= *vy*

**D. ***x* =* v*

(x^{2} + 3xy + y^{2}) dx − x^{2} dy = 0

Solve the following initial value problem:

(x^{2} + y^{2}) dx = 2xy dy, y (1) = 0

Solve the following initial value problem:

\[x e^{y/x} - y + x\frac{dy}{dx} = 0, y\left( e \right) = 0\]

Solve the following initial value problem:

\[\frac{dy}{dx} - \frac{y}{x} + cosec\frac{y}{x} = 0, y\left( 1 \right) = 0\]

Solve the following initial value problem:

(xy − y^{2}) dx − x^{2} dy = 0, y(1) = 1

Solve the following initial value problem:

\[\frac{dy}{dx} = \frac{y\left( x + 2y \right)}{x\left( 2x + y \right)}, y\left( 1 \right) = 2\]

Solve the following initial value problem:

x (x^{2} + 3y^{2}) dx + y (y^{2} + 3x^{2}) dy = 0, y (1) = 1

Solve the following initial value problem:

\[\left\{ x \sin^2 \left( \frac{y}{x} \right) - y \right\}dx + x dy = 0, y\left( 1 \right) = \frac{\pi}{4}\]

Solve the following initial value problem:

\[x\frac{dy}{dx} - y + x \sin\left( \frac{y}{x} \right) = 0, y\left( 2 \right) = x\]

Find the particular solution of the differential equation x cos\[\left( \frac{y}{x} \right)\frac{dy}{dx} = y \cos\left( \frac{y}{x} \right) + x\], given that when x = 1, \[y = \frac{\pi}{4}\]

Find the particular solution of the differential equation \[\left( x - y \right)\frac{dy}{dx} = x + 2y\], given that when x = 1, y = 0.

Show that the family of curves for which \[\frac{dy}{dx} = \frac{x^2 + y^2}{2xy}\], is given by \[x^2 - y^2 = Cx\]

A homogeneous differential equation of the form \[\frac{dx}{dy} = h\left( \frac{x}{y} \right)\] can be solved by making the substitution

Which of the following is a homogeneous differential equation?

Solve the following differential equation : \[\left[ y - x \cos\left( \frac{y}{x} \right) \right]dy + \left[ y \cos\left( \frac{y}{x} \right) - 2x \sin\left( \frac{y}{x} \right) \right]dx = 0\] .

Solve the differential equation: x dy - y dx = `sqrt(x^2 + y^2)dx,` given that y = 0 when x = 1.

**Solve the following differential equation:**

`"x" sin ("y"/"x") "dy" = ["y" sin ("y"/"x") - "x"] "dx"`

**Solve the following differential equation:**

`(1 + 2"e"^("x"/"y")) + 2"e"^("x"/"y")(1 - "x"/"y") "dy"/"dx" = 0`

**Solve the following differential equation:**

y^{2} dx + (xy + x^{2})dy = 0

**Solve the following differential equation:**

`"x" "dy"/"dx" - "y" + "x sin"("y"/"x") = 0`

**Solve the following differential equation:**

`(1 + "e"^("x"/"y"))"dx" + "e"^("x"/"y")(1 - "x"/"y")"dy" = 0`

**Solve the following differential equation:**

`"y"^2 - "x"^2 "dy"/"dx" = "xy""dy"/"dx"`

**Solve the following differential equation:**

`"xy" "dy"/"dx" = "x"^2 + "2y"^2, "y"(1) = 0`

**Solve the following differential equation:**

x dx + 2y dx = 0, when x = 2, y = 1

**Solve the following differential equation:**

`"x"^2 "dy"/"dx" = "x"^2 + "xy" + "y"^2`

**Solve the following differential equation:**

(9x + 5y) dy + (15x + 11y)dx = 0

**Solve the following differential equation:**

(x^{2} + 3xy + y2)dx - x^{2} dy = 0

**Solve the following differential equation:**

(x^{2} – y^{2})dx + 2xy dy = 0

**State whether the following statement is True or False: **

A homogeneous differential equation is solved by substituting y = vx and integrating it

Solcve: `x ("d"y)/("d"x) = y(log y – log x + 1)`

The solution of the differential equation `(1 + e^(x/y)) dx + e^(x/y) (1 + x/y) dy` = 0 is

A homogeneous differential equation of the `(dx)/(dy) = h(x/y)` can be solved by making the substitution.

Let the solution curve of the differential equation `x (dy)/(dx) - y = sqrt(y^2 + 16x^2)`, y(1) = 3 be y = y(x). Then y(2) is equal to ______.

If a curve y = f(x), passing through the point (1, 2), is the solution of the differential equation, 2x^{2}dy = (2xy + y^{2})dx, then `f(1/2)` is equal to ______.

The differential equation y' = `y/(x + sqrt(xy))` has general solution given by:

(where C is a constant of integration)

Find the general solution of the differential equation:

(xy – x^{2}) dy = y^{2} dx